Sweet potato (Ipomoea batatas) and hyacinth bean (Lablab purpureus) in combination provide greater suppression of mile-a-minute (Mikania micrantha) than either crop alone - Shen, Shicai; Xu, Gaofeng; Ma, Guangzong; Li, Diyu; Yang, Shaosong; Jin, Guimei; Clements, David Roy; Chen, Aidong; Wen, Lina; Cui, Yuchen; Chuan, Li; Zhang, Fudou; et al. (Frontiers in Plant Science, 2023)
In natural systems, diverse plant communities tend to prevent a single species from dominating. Similarly, management of invasive plants may be achieved through various combinations of competing species. We used a de Wit replacement series to compare different combinations of sweet potato (Ipomoea batatas), hyacinth bean (Lablab purpureus ) and mile-a-minute (Mikania micrantha) through measures of photosynthesis, plant growth, nutrient levels in plant tissue and soil, and competitive ability. Cultured alone sweet potato and hyacinth beans exhibited higher total biomass, leafstalk length, and leaf area than mile-a-minute. In mixed culture, either sweet potato or hyacinth bean or both together significantly suppressed the mile-a-minute parameters, i.e., plant height, branch, leaf, adventitious root, and biomass (P<0.05). Based on a significantly lower than 1.0 relative yield of the three plant species in mixed culture, we showed intraspecific competition to be less than interspecific competition. Calculated indices (relative yield, relative yield total, competitive balance index, and change in contribution) demonstrated a higher competitive ability and higher influence of either crop compared to mile-a-minute. The presence of sweet potato and hyacinth bean, especially with both species in combination, significantly reduced (P<0.05) mile-a-minute’s net photosynthetic rate (Pn), antioxidant enzyme activities (superoxide dismutase, peroxidase, catalase, and malondialdehyde), chlorophyll content, and nutrient content (N, P, and K). In soil with mile-a-minute in monoculture soil organic matter, total and available N, total and available K, and available P were significantly greater (P<0.05) than in soil with sweet potato grown in monoculture, but less than in soil with hyacinth bean grown in monoculture soil. Nutrient soil content was comparatively reduced for plant mixtures. Plant height, leaf, biomass, Pn, antioxidant enzyme activities, and plant and soil nutrient contents of sweet potato and hyacinth bean tended to be much greater when grown with two crops compared to in mixture with just sweet potato or hyacinth bean. Our results suggest that the competitive abilities of both sweet potato and hyacinth bean were greater than that of mile-a-minute, and also that mile-a-minute suppression was significantly improved via a combination of the two crops compared to either sweet potato or hyacinth bean alone.